The Effect of Product Quality and TV Advertising on Purchasing Decisions for Pepsodent Sensitive Expert: Pengaruh Kualitas Produk Dan Iklan Di Tv Terhadap Keputusan Pembelian Pepsodent Sensitive Expert - Puspa Leni; Jumiatul Mulya; Eliza Eliza (International Journal of Management and Business (IJMB), 2023)
This study aimed to analyze the effect of product quality and TV advertising on purchasing decisions for Pepsodent Sensitive Expert in Padang Panjang City. The number of respondents used as a sample size is 100 respondents. This type of research is associative research. The results of this study indicate that product quality and TV advertising partially have a positive and significant effect on purchasing decisions for Pepsodent Sensitive Expert in Padang Panjang City. Simultaneously, product quality and television advertising positively and significantly affect purchasing decisions for Pepsodent Sensitive Expert in Padang Panjang City, with an R2 value of 86.1%..